The Value of Invested Capital - Champernowne, D. G.; Kahn, R. F. (Review of Economic Studies, 1953)
D. G. Champernowne, R. F. Kahn; The Value of Invested Capital, The Review of Economic Studies, Volume 21, Issue 2, 1 January 1953, Pages 107–111, https://d